Structure of broad-scale management in the Vernadsky Station area - A. P. Fedchuk (Ukrainian Antarctic Journal, 2009)
The article is devoted to actual issues on methodological provisions for Antarctic activity. Geographical distribution and further diversification of human activities in this region became an environmental threat that needs more comprehensive approach for management in Antarctic in whole and specifically in the region of Ukrainian scientific interests. The functional structure of main Antarctic specially protected and managed areas is analyzed, the reasons of their high concentration along the north-west part of Antarctic Peninsula are shown. It is suggested that the region of Ukrainian scientific interests could be strengthened by a multiple use management system in order to avoid or reduce the risk of interference and minimise environmental impacts, plan and co-ordinate the existing and future activities the region. On the basis comparative-geographical analyses there were identified analogue areas similar to landscape structure (Anvers Island with adjacent islands) and component-based management structure (Deception Island). It is specified that basic measures for environmental protection should be the following: regulation sea-borne tourism, as well as coordination and stimulation research activities at representative sites which play a key role in regional ecosystem processes. It is suggested to develop a management plan by the environmental risk assessment procedures as well as step-by-step approach approved by German colleagues in the Fildes Peninsula Region, King George Island. The most comprehensive ecosystem study conducted within the Fildes Peninsula region provides a basis for further research which needs a long term environmental monitoring and information material compiling.